Subject Matter Outline To Accompany the Statement of "Concepts of Federal Income Taxation". (The Accounting Review, 1969)
Abstract This article presents the subject matter outline, a supplement to the statement of Concepts of Federal Income Taxation. The Subject Matter Outline is divided into ten sections, nine sections of which correspond with the nine major divisions of the "Concepts of Federal Income Taxation" the major sections of each have the same caption headings. Each division of the outline was made as complete as possible so the instructor could select the order in which he would present the material. It is felt that an understanding of the tax concepts, as emphasized in this outline, will make the study of taxation more meaningful and will give the student a more thorough base for future development of his knowledge of Federal income taxation. Hopefully, this outline will prove helpful in teaching the subject of income taxation.